On the initiation of macrovoids in polymeric membranes – effect of polymer chain entanglement - Hung, Wei-Lun; Wang, Da-Ming; Lai, Juin-Yih; Chou, Shang-Chih (Journal of membrane science, 2016)
The present work investigated the mechanism of macrovoid initiation in polymeric membranes, with focus on the initiation position of macrovoids. The results show that where macrovoids were initiated strongly depended on the polymer concentration in casting solution and the solvency for polymer of the solvent used. Comparing the results with the rheological properties of casting solutions, we observed a close relationship between the initiation position of macrovoids and the degree of polymer-chain entanglement in the casting solution. High degree of chain entanglement helped to suppress the occurrence of macrovoids. And low quality solvent enhanced chain entanglement and brought about environment not favored for macrovoid initiation. We also obtained results showing that the time needed to induce the phase separation of casting solution played an important role in initiation of macrovoids. A model was developed to take into account the effects of the degree of chain entanglement and the time needed to induce phase separation, by using the chain relaxation time to characterize the effect of chain entanglement and the time constant of the movement of phase separation front to quantify the time needed for phase separation. The model can quantitatively describe the relationship between the initiation position of macrovoids and the polymer concentration in casting solution for the polymeric membranes prepared in the present work. [Display omitted] •The important role of polymer chain entanglement in macrovoid initiation has been identified.•Initiation of macrovoids is related to two time scales: the relaxation time of polymer chains in casting solution and the time needed to induce the phase separation of casting solution.•A model can well describe the relationship between the initiation position of macrovoids and the polymer concentration in casting solution.